Юсупов поэмаларында метонимиялардың қолланылыўы (FAN va JAMIYAT, 2019)
The article is devoted to the study of using metonymies in the poems of the great Karakalpak People’s poet I. Yusupov, his skill in using metonymies. The author also studies the role of the poet’s works in the development of the modern Karakalpak literary language.